Bribery, Hold-Up and Bureaucratic Structure - John Bennett; Matthew D. Rablen (Institute of Labor Economics (IZA), 2018)
We analyze the provision of infrastructure by a foreign investor when the domestic bureaucracy is corrupt, but puts some weight on domestic welfare. The investor may pay a bribe in return for a higher provisional contract price. After the investment has been sunk, the bureaucracy may hold up the investor, using the threat of expropriation to demand a lower final price or another bribe. Depending on the level of care for domestic welfare, greater bureaucratic centralization may increase or decrease domestic welfare. Because of the threat of hold-up, bribery may result in greater domestic welfare than the honest benchmark does.
Keywords: D73; H11; 330; bribery; hold-up; renegotiation; bureaucratic structure; centralized bureaucracy; decentralized bureaucracy